Coronavirus COVID-19 [electronic resource] - United States. The White House; United States. Centers for Disease Control and Prevention; United States. Department of Homeland Security.Federal Emergency Management Agency (Washington, D.C. The White House; CDC; FEMA, 2020)
COVID-19 is an emerging, rapidly evolving situation. Get the latest public health information from this site.
UPMindanao University Library (UL)
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Open access publishing; Education, Higher; COVID-19 (Disease) -- Research -- Electronic information resources; COVID-19 (Disease) -- United States -- Electronic information resources; Open access publishing